Kajian Potensi Whey Yoghurt sebagai Bahan Alami Pencegah Jerawat - Rahman, A.; Taufik, E.; Purwantiningasih, S.; Purwanto, B. P. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2014)
Cheese processing always produce a liquid by product, called as whey. Whey contains 50% of milk nutrients, but currently in Indonesia whey is not used optimally. Whey contained some lactose, and can be used as fermented media. This study used cheese whey as a fermented media for Streptococcus thermopillus (StRRM01) and Lactobacillus bulgaricus (Lb-RRM01) called as Whey Yogurt (WY). WY compared to fresh whey (control) on this study for skin care, include of acne treatment. Data were analyzed by T-test on SPSS statictical program. The research showed that WY inhibited the growth of bacteria Propionibacterim acnes 4.35 mm, while there was no inhibition on control (P <0.05). Fermentation process increased the antioxidant activity for 27.7%. WY had the good potential for the acne treatment. This study showed that whey had a value-added,furthermore in the future might be used to develop into a natural ingredient cosmetics for skin care.